Protective effects of alfalfa saponins on oxidative stress-induced apoptotic cells. Issue 9 (1st September 2020) - Cui, Yalei; Liu, Boshuai; Sun, Xiao; Li, Zidan; Chen, Yanyan; Guo, Zhiguo; Liu, Hua; Li, Defeng; Wang, Chengzhang; Zhu, Xiaoyan; Shi, Yinghua
Abstract : Alfalfa saponins defend against oxidative stress by enhancing the antioxidant system and further inhibit cell apoptosis by activating the MAPK signaling pathway. Abstract : As is known, alfalfa saponins can be used as a feed additive in a pig's diet and the addition of alfalfa saponins to a pig's diet could improve its antioxidant capacity. However, the mechanism by which alfalfa saponins exert their antioxidant effects has not been studied. To address this issue, H2 O2 -induced rat intestinal epithelial cells were used to establish an oxidative stress model to explore the protective mechanism of alfalfa saponins in this study. The results demonstrated that alfalfa saponins could rescue the cell proliferation activity, elevate the amount of antioxidant enzymes and downregulate the release of MDA and LDH in H2 O2 -induced cells. The antioxidant activity of alfalfa saponins was achieved by restoring GSH homeostasis. Further results demonstrated that alfalfa saponins could inhibit cell apoptosis through activating the MAPK signaling pathway. These results elucidated the mechanism by which alfalfa saponins exert their antioxidant effects and provided a potential strategy for alleviating oxidative stress in monogastric animals.